Alterity-space: national spatiality in Lasnamäe, Estonia - Shaharyar, Nawal (Frontiers in Political Science, 2024)
This research investigates the relationship between the city and the state in framing the national belonging of space as arenas of inclusion and difference within the nation. It is argued that bringing Isin and Lefebvre into dialogue allows for a genealogical analysis of space as a social product imbued in and constituted by narratives of national inclusion (or exclusion). This research develops the concept of alterity-space as a distinct spatial category in which the constitution of citizenship is inscribed on socially produced space. This alterity-space refers to categories of difference as an internal other of space at odds with the space of the nation. Alterity-space as a concept invites reflection on how state engagement, competing symbolisms, narratives, and interactions produce spatiality and create mechanisms of othering that obscure other articulations of national belonging in space. This approach is illustrated through a genealogical examination of Lasnamäe, an urban district at the heart of Estonia’s capital. In the constitution of national, ecological, digital, and European identities, Lasnamäe is positioned as an alterity-space to Tallinn and Estonia. This positioning reflects how space itself becomes imbued as an immediate other at odds with Estonia’s past and future of national belonging.